Grid integration of wind energy conversion systems = - Heier, Siegfried (Wiley, 1992)
Coverage includes the electrical and mechanical components of wind power plants making the book an asset to graduate students of both engineering disciplines. Illustrated guidance on the design, construction, planning and installation of wind plants will benefit engineers and consultants involved in wind energy development